Morale in Old Age and Its Association with Sociodemographic, Social, and Health-Related Factors in Different Age Groups. (1st August 2020) - Näsman, Marina; Niklasson, Johan; Saarela, Jan; Nygård, Mikael; Olofsson, Birgitta; Gustafson, Yngve; Nyqvist, Fredrica
Abstract : Morale can be viewed as a future-oriented optimism or pessimism regarding challenges associated with aging and is closely related to subjective well-being. Promoting morale in old age could be considered to have important implications for aging well, and increased knowledge about morale in different stages of old age is needed. Hence, the aim of this study was to investigate factors associated with morale in different age groups among old people. Data were derived from a survey conducted in 2016, as a part of the Gerontological Regional Database (GERDA). The sample consisted of 9, 047 individuals aged between 65 and 86 years from Ostrobothnia and Southern Ostrobothnia in Finland, and Västerbotten in Sweden. Morale was measured with the Philadelphia Geriatric Center Morale Scale (PGCMS) and regressed upon a number of sociodemographic, social, and health-related factors using linear regression analyses. The results showed that older age was an independent factor explaining lower level of morale. Additionally, the sociodemographic, social, and health-related variables could explain a large proportion of the variance in morale. Perceived loneliness, having gone through a crisis in life, poor self-rated health, and depression were associated with lower morale, and sleeping well with higher morale, in all age groups. Furthermore, the oldest age groups seem to be more exposed to several risk factors of lower morale identified in this study. Multidimensional interventions targeting especially social and mental health and the oldest-old could therefore be recommended.